Caracterização dos acidentes escorpiônicos pediátricos no Oeste Paulista - SANTELLO, Samara Bertin Suguitani (2020)
Objective: Map the pediatric care related to scorpionism highlighting the serious cases, and compare with variables of age, sex, sting location and seasons of the year. Method: Data were collected from medical records and Epidemiological Surveillance Notification form at SINAN (Information System for Notification of Grievances), construction of a generalized additive model using “quasi-poisson” regression, capable of controlling data overdispersion when considering that the variance is a linear function of the media. Cubic smoothing functions of the tipe Spline considering 80 knots were inserted to model the possible curves associated to the seasons of the year. The number of knots was defined by cross variation, in which diferente scenarios were tested for choosing the vallue capaple of maximizing the adjusted coefficient of determination (R2) of the regression. Chi-square test and estimate of ODDS RATIO were used to evaluate the possible factors associated to the major acidentes x mild and moderate accidents. The variables: sex, age up to 10 years old, seasons of the year and stinging in extremities (hands and feet) were evaluated. All analyzes conducted in program R, adopting a 5% level of significance. Results: There were 236 children under 18 years old notified in the investigated period. Which 34 cases were classsified serious and 202 cases were classified as mild to moderate. There was a predominance of children up to 10 years old, and also a significant increase in cases from 2015. Conclusion: It was seen that younger children are related to more cases, and age ove 10 years old was showed was a protective factor.